Developing a product–service system through a productisation strategy: a case from the 3PL industry. Issue 6 (19th March 2018) - Lahy, Andrew; Li, Ai Qiang; Found, Pauline; Syntetos, Aris; Wilson, Mike; Ayiomamitou, Nicole
Abstract : A Product–Service System (PSS) is created by combing a tangible product and an intangible service into one integrated offering. Thus, a PSS can be achieved by a production company adding intangible services to a product using a servitisation strategy or by a service company adding a tangible product to a service by means of a productisation strategy. The focus of this paper is on the latter. Our work demonstrates a significant gap in the literature in this area. To address this, we adapt an existing PSS conceptual framework as a means to identify the driving and restraining forces considered by a service company as it explored the possibility of pursuing a PSS productisation strategy. The conceptual framework is applied in an exploratory case study with a 3PL service provider. Application of the framework reveals new driving and restraining forces not previously discussed in the literature. Furthermore, it allows a preliminary quantification of the driving and restraining forces using a force field analysis approach. Our work contributes towards the expansion of the empirical knowledge base in the area of PSS.